The Actual Practice of Breast Self-Examination among Sample of Iraqi Patients with Breast Cancer - Al-Alwan, Nada A. S. (AL-Kindy College Medical Journal, 2020)
Background : To assess the actual practice of breast self-examination (BSE), as an early detection tool for breast cancer, among a sample of patients affected with breast cancer in Iraq.Methods: A random sample of 200 female patients with breast cancer was analyzed to evaluate the extent of their actual practice of breast self-examination before the diagnosis of the disease.  The examined variables included the age of the patients, marital status, education, occupation, smoking habit, family history of cancer, frequency of gravidity, parity and abortions. Results: The age of patients ranged from (24-70) years with a mean age of 48 years. The highest frequency of the examined sample (24%) was noted in the age group   (50-54) years. The majority of the patients (89%) were married, 33% had university degree and 57% were employed. While 46% of the patients had a family history of cancer, in 33.5% the breast was involved. Only 5.5% of the total number of patients had practiced BSE regularly before the diagnosis of breast cancer, 57.5% had carried out the procedure randomly while 37% did not perform BSE at all during their lives.  The study illustrated that the level of education, occupation and family history of cancer had significant roles in the practice of BSE. Conclusions: The findings of this study emphasize the urgent need for promoting screening in our society through strengthening practical policy decisions to raise the level of public awareness among the Iraqi women towards the adoption of simple approaches for early detection of breast cancer.